Epidemiology of gastrointestinal proliferative neoplastic-like lesions and tumors in dogs and cats: a retrospective study in two Romanian reference laboratories - Andrada Negoescu; Cristina-Diana Borfalău; Claudiu Gal; Marian Taulescu; Cornel Cătoi (Cluj Veterinary Journal)
Gastrointestinal neoplasms are rare in dogs and cats, primarily comprising adenocarcinomas, lymphomas, leiomyomas, leiomyosarcomas, and gastrointestinal stromal tumors (GISTs). In the current literature  epidemiological data  are scars. The aim of  this study was to identify the epidemiological  and the pathological features of these neoplasms in dogs and cats. Epidemiological data were collected from the databases of two laboratories in Romania, covering a period of 10 years. A total of 192 cases of neoplastic and neoplastic-like lesions were selected and subjected to statistical analysis. Older animals were more predisposed for chronic hypertrophic pyloric gastropathy (CHPG) (mean age of 11.14 years) and gastric polyps (mean age of 9.6 years), while younger individuals showed a higher incidence for feline gastrointestinal eosinophilic sclerosing fibroplasia (FGIESF), with a mean age of 7.25 years for the lesions located in the stomach and 5.25 years in the intestine. Additionally, CHPG and FGIESF were more prevalent in males. Dogs were the main species affected by benign neoplasms, including adenomas (22%) and adenomatous polyps/pedunculated adenomas (5%), primarily located in the anorectal junction, as well as leiomyomas (8%) with gastric involvement. In dogs, malignant neoplasms accounted for 69%, with adenocarcinomas representing 39%, followed by lymphomas (12%), and GIST (9%). In cats, 98.82% of neoplasms were represented by malignant tumors, with lymphomas being the most frequently diagnosed (77%). Both adenocarcinomas in dogs and lymphomas in cats were more common in males, accounting for 61.76% and 52.31% of cases, respectively, with the intestine being the most frequently affected site. This is the first epidemiological study in Romania to examine both the gastrointestinal tract in dogs and cats, including neoplastic-like lesions. The definitive diagnosis of gastrointestinal masses requires histological and molecular analyses.